2018
DOI: 10.1093/jcr/ucy069
|View full text |Cite
|
Sign up to set email alerts
|

When Busy Is Less Indulging: Impact of Busy Mindset on Self-Control Behaviors

Abstract: An increasing number of consumers, in recent times, have reported feeling busier than ever. The current research examines how the subjective perception of busyness-which is referred to as a busy mindset in the current research-impacts consumers' decision-making. Building on different streams of research in sociology and self-view, the current research proposes that a busy mindset bolsters people's sense of self-importance, which, in turn, can increase self-control. Thus, a busy mindset is predicted to facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 71 publications
0
78
0
1
Order By: Relevance
“…An emergent area of research is the consumption of time (Bellezza, Paharia, & Keinan, ; Kim, Wadhwa, & Chattopadhyay, ; Wilcox, Laran, Stephen, & Zubcsek, ). When people perceive that they are busy they are more likely to exert self‐control if they associate being busy with being important (Kim et al, ). Nevertheless, people who are busy are more likely to experience negative affect and stress (Kerfoot, ).…”
Section: The Future Of Self‐control: Research Implicationsmentioning
confidence: 99%
“…An emergent area of research is the consumption of time (Bellezza, Paharia, & Keinan, ; Kim, Wadhwa, & Chattopadhyay, ; Wilcox, Laran, Stephen, & Zubcsek, ). When people perceive that they are busy they are more likely to exert self‐control if they associate being busy with being important (Kim et al, ). Nevertheless, people who are busy are more likely to experience negative affect and stress (Kerfoot, ).…”
Section: The Future Of Self‐control: Research Implicationsmentioning
confidence: 99%
“…This investigation also contributes to indulgent consumption literature. Ample evidence has shown that indulgent behavior is caused by having low self-control or an amiable nature (Chang and Chu, 2020;Kim et al, 2018;Simonson, 2002a, 2002b;Nenkov and Scott, 2014;Wiggin et al, 2018). We show that sex cues can evoke a similar effect in various indulgent behaviors or choices.…”
Section: Introductionmentioning
confidence: 50%
“…On the other hand, those living in poverty and under other systemic conditions of scarcity simply have less time (Mullainathan & Shafir, 2013), making it more likely that they will interpret experienced difficulty as a sign of impossibility rather than importance. In some cases time scarcity can be experienced as a feeling of busyness, which can motivate people to prioritize difficult tasks that feel important (Ebrahimi et al, 2017;Kim et al, 2019;Wilcox et al, 2016). However, the motivating effects of busyness are more likely to be felt by people of higher socioeconomic status who have greater control over how they use their time, while those who are more chronically resource-scarce are less able to restructure their time to prioritize important goals when busy (Mullainathan & Shafir, 2013).…”
Section: How (Perceived) Difficulty and Time Perception Interact To Influence Goal Pursuitmentioning
confidence: 99%